A REVISED METHOD FOR OBSERVING THE SAME NANNOFOSSIL SPECIMENS WITH SCANNING ELECTRON MICROSCOPE AND LIGHT MICROSCOPE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1989)
A new method for the observation of the same nannofossil specimens with scanning electron microscope and light microscope, involving the use of a grid, is described. This technique provides a complete analysis of the morphological diagnostic characteristics of calcareous nannofossils and other microfossils.
Keywords: New investigation technique; Scanning electron microscope and light microscope; Calcareous nannofossils.